2017
DOI: 10.1590/18069657rbcs20160218
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Matter Quality in Jatropha spp. Plantations in Different Edaphoclimatic Conditions

Abstract: ABSTRACT:The substitution of native vegetation by agricultural ecosystems can change the quantity and quality of soil organic matter (SOM), and the intensity of these changes depends on the soil type, climate, and land use. The objective of this study was to evaluate the quality of organic matter in chronosequences of Jatropha cultivation in contrasting soil and climatic conditions. Soil samples were evaluated at depths of 0.00-0.10, 0.20-0.30, and 0.80-1.00 m in chronosequences located in Planaltina, Distrito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
0
0
4
Order By: Relevance
“…Some reasons favor soil microbial biomass under native vegetation: a) higher plant diversity and lowest variation in temperature and moisture (Carvalho et al 2018); b) higher organic inputs and better quality and quantity of plant litter (Lopes et al 2010). These results are in agreement with previous studies, which have found higher soil microbial biomass under native vegetation than cropland (Viana et al 2011;Novak et al 2017;Freitas et al 2017). D' Andréa et al (2002 evaluated Brazilian oxisols under different land use and found a decrease of 49 and 73% in the MBC under pastures and cropland, respectively, as compared with native vegetation.…”
Section: Resultssupporting
confidence: 90%
“…Some reasons favor soil microbial biomass under native vegetation: a) higher plant diversity and lowest variation in temperature and moisture (Carvalho et al 2018); b) higher organic inputs and better quality and quantity of plant litter (Lopes et al 2010). These results are in agreement with previous studies, which have found higher soil microbial biomass under native vegetation than cropland (Viana et al 2011;Novak et al 2017;Freitas et al 2017). D' Andréa et al (2002 evaluated Brazilian oxisols under different land use and found a decrease of 49 and 73% in the MBC under pastures and cropland, respectively, as compared with native vegetation.…”
Section: Resultssupporting
confidence: 90%
“…AR: área de referência; SM8: plantio de soja em cultivo mínimorecente; SM18: plantio de soja em cultivo mínimo -antigo ......................................................................................................... 55 Tabela 13 -Contribuição de Carbono oriundo de plantas de ciclo fotossintético C4 nas áreas de pastagem estudadas em Belterra, PA. AR: área de referência; PN4: pastagem nominal; PM6: pastagem melhorada . ............................................................................................................. 27 Figura 5 -Área plantada (ha) de grãos no município de Belterra, PA entre 2000a 2017 Figura 10 -Grau de humificação da MOS (HFIL) em amostras de solo das áreas de estudo (Belterra, PA AR: área de referência; PN4: pastagem nominal; PM6: pastagem melhorada; SM8: plantio de soja em cultivo mínimorecente; SM18: plantio de soja em cultivo mínimoantigo ..…”
Section: Lista De Tabelasunclassified
“…O melhoramento da pastagem além de aumentar o estoque de C no solo (CERRI et al, 2007;MAIA et al, 2009;BUSTAMANTE et al, 2012;CERRI et al, 2018) também é necessário para melhorar a produtividade. Silva et al (2004) Rosa et al (2005), Favoretto et al (2008), Freitas et al (2017) e Oliveira (2018). Vale ressaltar que o processo de humificação da MOS também está relacionado à condição edafoclimática do local, ao tipo de material de origem, assim como ao manejo aplicado na área (BAYER et al, 2002).…”
Section: Fracionamento Físico Da Mosunclassified
See 1 more Smart Citation
“…Análises de variância (ANOVA) foi utilizada para checar os efeitos do manejo de solo sobre a cultura do milho, considerando um delineamento experimental aleatório, com cinco repetições (Cherubin et al, 2016;Freitas et al, 2017;Signor et al, 2018). Todas as análises foram executadas no software estatístico SAS.…”
Section: Análise Estatísticaunclassified